The Correlation Between The Application of Shadowing Technique and Students’ Pronunciation Skill at Grade XII of SMAN 1 Pekanbaru - Rifanya Permata Abdi; Qonaah Nuryan Arif; Esti Raihana (Lembaga Pengembangan Kinerja Dosen, 2025)
This research examines the correlation between the application of the shadowing technique and students’ pronunciation skill among grade XII students at SMA Negeri 1 Pekanbaru. The research was motivated by the observation that many students still struggle to produce accurate English sounds in both segmental and suprasegmental aspects, such as vowels, consonants, stress, and intonation. This research employed a quantitative correlational design. The population consisted of 108 grade XII students, who were also taken as the total sample. Data were collected using two instruments, namely a shadowing technique questionnaire and a pronunciation test assessed with an analytic rubric. Data analysis was conducted using the Pearson Product Moment Correlation through SPSS version 23 after performing validity, reliability, normality, and linearity tests. The results revealed that the Pearson correlation coefficient between the shadowing technique and students’ pronunciation skill was r = 0.281 with a significance value of p = 0.003. This indicates a positive and low correlation that is statistically significant. Therefore, the alternative hypothesis (Ha) is accepted. In other words, the use of the shadowing technique shows a significant correlation with students’ pronunciation skill. Thus, it can be concluded that there is a significant positive correlation between the application of the shadowing technique and students’ pronunciation skill among grade XII students at SMA Negeri 1 Pekanbaru.